2020
DOI: 10.3390/ijerph17072395
|View full text |Cite
|
Sign up to set email alerts
|

Movement in High School: Proportion of Chinese Adolescents Meeting 24-Hour Movement Guidelines

Abstract: The purposes of this study were (a) to examine the proportions of adolescents in China who partially or fully meet three 24-h movement guidelines on physical activity, screen-time, and sleep duration and (b) to examine whether there were gender differences in the proportion of boys and girls meeting these guidelines. The sample was made up of high school adolescents from an eastern province of China (N = 1338). The participants completed a self-reported survey on demographic variables and weekly health behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…Additionally, healthy weight individuals were more likely to meet the sleep (23.1%) and MVPA (15.4%) guidelines compared to their overweight (16.1% and 9.7%) and obese (0% and 11.1%) counterparts, respectively. Poor adherence to the screen time recommendation of <2 h of recreational screen time per day is commonly reported but was not assessed in this study [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, healthy weight individuals were more likely to meet the sleep (23.1%) and MVPA (15.4%) guidelines compared to their overweight (16.1% and 9.7%) and obese (0% and 11.1%) counterparts, respectively. Poor adherence to the screen time recommendation of <2 h of recreational screen time per day is commonly reported but was not assessed in this study [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most existing studies have reported that less than 10% of adolescents met the 24-Hour Movement Guidelines [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These aforementioned studies have found inconsistent results in the proportion of adolescents who meet the 24-Hour Movement Guidelines, which have ranged from 0.3% to 2.0% in Asian [ 14 , 21 , 26 ] 3.1% in South Americans [ 25 ], 2.2% to 9.4% in North Americans (ranging from 2.2% to 5.2% in Canadian and from 5.0% to 9.4% in American) [ 4 , 15 , 16 , 18 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ], and from 1.7% to 2.2% in European [ 17 , 19 , 27 ]. Most adolescents met sleep duration recommendations [ 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 25 ,…”
Section: Introductionmentioning
confidence: 99%
“…These aforementioned studies have found inconsistent results in the proportion of adolescents who meet the 24-Hour Movement Guidelines, which have ranged from 0.3% to 2.0% in Asian [ 14 , 21 , 26 ] 3.1% in South Americans [ 25 ], 2.2% to 9.4% in North Americans (ranging from 2.2% to 5.2% in Canadian and from 5.0% to 9.4% in American) [ 4 , 15 , 16 , 18 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ], and from 1.7% to 2.2% in European [ 17 , 19 , 27 ]. Most adolescents met sleep duration recommendations [ 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 28 , 29 , 30 , 31 , 32 ], whereas less than half of adolescents met physical activity [ 13 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the con rmed health bene ts associated with meeting the recommendations for PA, SB, and sleep, worldwide adherence to the combined movement guidelines is low among children and adolescents [19][20][21][22][23][24][25][26][27][28]. Unfortunately, over the last decades, scienti c evidence has documented a negative secular trend for engaging in regular PA, limiting SB, and obtaining adequate sleep [29][30][31].…”
Section: Introductionmentioning
confidence: 99%